Vigilance and restraint in the common law of judicial review / Dean R. Knight. - Knight, Dean R. (Dean Robert) (Cambridge studies in constitutional law., 2018)
The mediation of the balance between vigilance and restraint is a fundamental feature of judicial review of administrative action in the Anglo-Commonwealth. This balance is realised through the modulation of the depth of scrutiny when reviewing the decisions of ministers, public bodies and officials. While variability is ubiquitous, it takes different shapes and forms. Dean R. Knight explores the main shapes and forms employed in judicial review in England, Canada, Australia and New Zealand over the last fifty years. Four schemata are drawn from the case law and taken back to conceptual foundations, exposing their commonality and differences, and each approach is evaluated. This detailed methodology provides a sound basis for decisions and debates about how variability should be brought to individual cases and will be of great value to legal scholars, judges and practitioners interested in judicial review.